2013
DOI: 10.2463/mrms.2012-0095
|View full text |Cite
|
Sign up to set email alerts
|

Correlations between Apparent Diffusion Coefficient Values and Prognostic Factors of Breast Cancer

Abstract: Purpose: We investigated possible correlations between apparent diŠusion coe‹cient (ADC) values and prognostic factors of breast cancer.Methods: We retrospectively evaluated 81 patients who underwent magnetic resonance (MR) imaging of the breast and were diagnosed pathologically with invasive ductal carcinoma (IDC) not otherwise speciˆed with invasive foci one cm or larger. We excluded ductal carcinoma in situ and IDC with invasive foci smaller than one cm because small lesions decrease the reliability of sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
45
4

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(52 citation statements)
references
References 31 publications
(26 reference statements)
3
45
4
Order By: Relevance
“…Choi et al (30) did not report a correlation between the Her2 and ADC values in their study with 335 patients with invasive ductal carcinoma. Similarly, Kamitani et al (36) did not report a correlation between the Her2 and ADC values in their study with 81 patients with invasive breast cancer. Although we found no statistical significance in terms of ER and PR values and Her2 values compared with the literature, the mean ADC values were much lower in patients with negative ER, PR and Her2 than in the patients with positive ER, PR and Her2.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…Choi et al (30) did not report a correlation between the Her2 and ADC values in their study with 335 patients with invasive ductal carcinoma. Similarly, Kamitani et al (36) did not report a correlation between the Her2 and ADC values in their study with 81 patients with invasive breast cancer. Although we found no statistical significance in terms of ER and PR values and Her2 values compared with the literature, the mean ADC values were much lower in patients with negative ER, PR and Her2 than in the patients with positive ER, PR and Her2.…”
Section: Discussionmentioning
confidence: 69%
“…The results of the studies reported in the literature are inconsistent. The mean ADC values with very small differences were significant in some studies but not significant in others (31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41). Therefore, we believe large series with the participation of more patients are needed in this regard.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Previously, it has been reported that positive breast cancer had significantly higher ADC values in comparison to Her2 negative carcinomas [16,17]. However, Kamitani et al showed no correlation of ADC and Her2 status [18].…”
Section: Accepted Manuscriptmentioning
confidence: 97%
“…Additionally, as for the step of screening, a flow chart of the study selection process was displayed in Figure 1. Initially, a total of 603 papers were selected from the 9 databases through screening the title and key words (Nakajo et al, 2010;Razek et al, 2010;Jeh et al, 2011;Nakai et al, 2011;Choi et al, 2012;Fornasa et al, 2012;Luo et al, 2012;Kamitani et al, 2013;Luo et al, 2013). Followed by excluding the duplicates (n=2), letters, reviews or meta-analysis (n=128), non-human studies (n=137), and the studies not related to research topics (n=145), the left studies (n=191) were reviewed and additional 179 studies were excluded in that they were not case-control or cohort study (n=48), not relevant to diffusion MRI (n=62), or not relevant to BC (n=69).…”
Section: Included Studiesmentioning
confidence: 99%